PALLADIUM, A PROGRAM TO MODEL THE CHROMATOGRAPHIC SEPARATION OF THE PLATINUM-GROUP ELEMENTS, BASE METALS AND SULFUR IN A SOLIDIFYING PILE OF IGNEOUS CRYSTALS - Boudreau A.E. (My University, 2004)
The formation of platinum-group-element (PGE) deposits in layered intrusions involves an interplay of sulfide saturation and modifications that might be caused by migrating silicate liquid and volatile fluid. The program PALLADIUM has been written to illustrate the chromatographic effects occurring, in a pile of igneous Crystals + liquid in a fractionating magmatic system, with a pile of cumulates that is both growing in thickness while also undergoing compaction, solidification and possible separation and migration of a volatile fluid phase. The program links compaction-driven mass transport with conductive cooling and compositional evolution controlled by equilibrium partitioning between phases. The elements S, Pd, Ir, Cu and Ni are assumed to follow simple partitioning behavior among the potential phases that include immiscible sulfide liquid, silicate liquid, volatile fluid. and I'd metal. All other precipitated solids are included in the solid matrix. The initial composition of the magma, compaction parameters and other variables can be set by the user. Two examples involving the crystallization of a "dry" and a "wet" magma are presented to illustrate the utility of the program. Both cases illustrate how chromatographic and reaction effects can lead to chromatographic separation of the elements aid the formation of metal alloys and other PGE-rich, S-poor phases beneath sulfide zones. as are observed in many PGE deposits. The principal difference between the "dry" magmatic precipitation Of Sulfide as a cotectic phase and those sulfides arising from fluid migration in a crystallizing "wet" pile of crystals is that the former cannot exceed cotectic proportions of sulfide unless there is preferential settling of sulfide, and the Pd metal zone is ephemeral. In contrast. the latter mechanism can produce sulfide-enriched zones in which Sulfide abundance exceeds expected cotectic levels of saturation.
Keywords: platinum-group-element deposits; geochemical modeling; layered intrusion; geochemical program; PALLADIUM